Building School Climate As A Learning Organization - Fauzan Fauzan; Moh. Dannur; Aldo Redho Syam; Mada Sutapa; Fajar Hendro Utomo; Alfiansyah Alfiansyah (Aqlamuna: Journal of Educational Studies, 2024)
The success of learning activities is largely determined by the climate and culture at school. The formation of a climate and culture that supports optimal learning activities in schools is also determined by the ability of all school stake holders, especially teachers as the main actors in teaching at school. The nature of learning in schools is not only inherent in students, but it is a must for all components, teachers, staff, and students. Therefore, all school components must understand the importance of the concept of school as a learning organization so that their capabilities increase in line with the changes and challenges of the times. The concept of learning organization coined by Peter Senge with five main principles that become the main pillars of the learning organization are personal mastery, mental models, shared vision, team learning, and systems thinking. These five principles are interrelated and reinforced in the practice of education to create a school as a learning organization. This study aims to emphasize and understand the cultivation of the five principles of Peter Senge's learning organization so as to create a learning climate and culture in schools. Abstrak Keberhasilan kegiatan pembelajaran sangat ditentukan oleh iklim dan budaya di sekolah. Terbentuknya iklim dan budaya yang mendukung optimalnya kegiatan pembelajaran di sekolah juga ditentukan oleh kemampuan seluruh stake holder sekolah terutama guru selaku aktor utama dalam pengajaran di sekolah. Hakikat belajar di sekolah tidak hanya melekat dalam diri siswa, tetapi menjadi keharusan bagi seluruh komponen, guru, staf, dan siswa. Karenanya, seluruh komponen sekolah harus memahami pentingnya konsep sekolah sebagai organisasi pembelajar agar kapabilitas mereka meningkat searah perubahan dan tantangan zama. Konsep learning organization yang dicetuskan oleh Peter Senge dengan lima prinsip utama yang menjadi pilar utama organisasi pembelajar yaitu personal mastery, mental models, shared vision, team learning, dan systems thinking. Kelima prinsip ini saling terkait dan menguatkan dalam praktek Pendidikan untuk menciptakan sekolah sebagai organisasi pembelajar. Kajian ini bertujuan memberikan penekanan dan pemahaman penanaman ke lima prinsip learning organization Peter Senge sehingga tercipta iklim dan budaya belajar di sekolah